Lymphadenopathy : Histopathological evaluation of 90 Cases in Chittagong - Chowdhury, Md Babul Osman; Ahmed, ASM Mostaque; Chowdhury, Abhijit (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Lymphadenopathy is one of the common clinical presentation of patients suffering from different disease processes. Lymphnode enlargement may be due to reactive changes, tuberculosis, sarcoidosis, Hodgkin lymphoma, Non Hodgkin lymphoma, Metastatic deposits etc. Histopathological examination of the enlarged lymphnode is the gold standard method to ascertain the cause of the enlargement. The objective of our study was to explore the causes of lymphadenopathy in the population of Chittagong. The study was conducted in the department of Pathology, Chattagram Maa-O-Shishu Hospital Medical College, Chittagong during January 2012 to July 2014. A total of 90 (Ninety) lymphoid tissue specimens were received and Hematoxilin Eosin stained histopathological slides were prepared and microscopic examination was done. The most common morphologic changes of lymphadenopathy noted was reactive hyperplasia (36.66%) and other causes included were tuberculosis (27.77%), metastasis (20%), Non-Hodgkin lymphoma (7.77%), Hodgkin lymphoma (4.44%) and suppurative lymphadenitis (3.33%). Our observations are supported by some other national and international studies on lymphadenopathy. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22874 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 19-21